Enhanced photoelectrical response of thermodynamically epitaxial organic crystals at the two-dimensional limit - Cao, Min; Zhang, Cong; Cai, Zhi; Xiao, Chengcheng; Chen, Xiaosong; Yi, Kongyang; Yang, Yingguo; Lu, Yunhao; Wei, Dacheng (Nature communications, 2019)
Owing to strong light-matter interaction, two-dimensional (2D) organic crystal is regarded as promising materials for ultrasensitive photodetectors, however it still received limited success due to degraded photoelectrical response and problems in controllable growth. Here, we find the growth of 2D organic crystal obeys Gibbs-Curie-Wulff law, and develop a seed-epitaxial drop-casting method to grow millimeter-sized 1,4-bis(4-methylstyryl)benzene 2D crystals on SiO 2 /Si in a thermodynamically controlled process. On SiO 2 /Si, a distinct 2D limit effect is observed, which remarkably enhances internal photoresponsivity compared with bulk crystals. Experiment and calculation show the molecules stack more compactly at the 2D limit, thus better molecular orbital overlap and corresponding changes in the band structure lead to efficient separation and transfer of photo-generated carriers as well as enhanced photo-gating modulation. This work provides a general insight into the growth and the dimension effect of the 2D organic crystal, which is valuable for the application in high-performance photoelectrical devices. To realize efficient optoelectronic devices based on two-dimensional (2D) organic crystals, optimizing the photoelectrical response and growth of these materials at the 2D limit is vital. Here, the authors report enhanced internal photoresponse in large-area 2D crystals using a novel growth method.